Head Louse (Pediculus humanus capitis) Remains in a Louse Comb from the Roman Period Excavated in the Dead Sea Region - Mumcuoglu, Kosta Y. (Israel exploration journal, 2011)
Two wooden louse combs, most probably from the Roman period, excavated in the 'Cave of the Pool', at the western end of the Naḥal David stream in the ʿEn Gedi oasis near the Dead Sea, were examined for the presence of head louse remains. In one of the combs, the head and the apical part (tarsus, tibia and femur) of one of the legs of a head louse were found. On the basis of measurements and a comparison to today's head lice, this louse was identified as belonging to the first nymphal stage.